In situ observation on the formation of intermetallics compounds at the interface of liquid Al/solid Ni. (15th March 2017) - Ding, Zongye; Hu, Qiaodan; Lu, Wenquan; Sun, Siyu; Xia, Mingxu; Li, Jianguo
Abstract: The growth of intermetallic compounds (IMCs) in liquid Al were observed on Ni substrate through synchrotron radiation real-time imaging technology. The results provided direct experimental evidence of the diffusion sequence of solid Ni and the growth mechanisms of the IMC layer. Through the snapped images, it was found that the Al3 Ni2 layered phase formed first in cooling stage, then the formation of irregular Al3 Ni phase through peritectic reaction. The growth of Al3 Ni2 layer was mainly controlled by diffusion. Graphical abstract: